Comparative study of the effect of different aqueous solutions on the physicochemical elements of solid medical waste in Nouakchott case of the Amitie hospital. - Ammar, Mohamed Bouna; Dick, Brahim Ahmed; Sid, Yahya Maham Ould; Fekhaoui, Mohamed (Jour Med Resh and Health Sci, 2022)
The management of hospital waste in health structures is of vital importance because this waste poses a real public health problem. A comparative study of the treatment of solid waste by different aqueous media such as drinking water, distilled water and alcoholic distilled water is carried out during the period from August to December 2019. This study has shown that the Physico-chemical composition of solid waste discharges from the Nouakchott Friendship Hospital in Mauritania has high pollutant loads, and has also demonstrated that these discharges are very rich in organic, mineral and particulate substances. The physico-chemical parameters analyzed are: pH, Temperature, Conductivity, and MES. All the analysis parameters meet the standards for wastewater, except the MES.